DIALOGUE OF CULTURES AS AN ORGANIC PRINCIPLE FOR FORMING TOLERANCE IN PRESCHOOL CHILDREN (Multidisciplinary Journal of Science and Technology, 2024)
International conflicts as challenges of the time actualize the problem of finding peaceful coexistence and international harmony. The importance of developing tolerance from childhood requires modern methods of pedagogical influence that have deep methodological and cultural-historical foundations. These include the principle of dialogue of cultures, which promotes the development of tolerant feelings and views based on the dialogical interaction of individuals, different mentalities, and works of art.